THE ROLE OF TECHNOLOGY-ENHANCED INSTRUCTION IN DEVELOPING ENGLISH PRONUNCIATION SKILLS AMONG UZBEK HIGH SCHOOL STUDENTS - Otabaev Muzaffar Ne'matullayevich (Bright Mind Publishing, 2025)
Mastering pronunciation is one of the most challenging aspects of English language learning for Uzbek high school students, particularly due to structural differences between the two languages and limited exposure to authentic English input. Recent advancements in educational technology, including artificial intelligence supported learning systems, have created new opportunities to improve pronunciation instruction. This study examines how technology-enhanced teaching methods support the development of English pronunciation, analyzes the typical difficulties faced by Uzbek learners, and evaluates the effectiveness of digital and AI-driven tools in comparison with traditional instruction. The findings suggest that the thoughtful integration of technology, particularly AI-based pronunciation feedback systems, can substantially improve learners’ intelligibility, confidence, and communicative competence.
Keywords: Technology-enhanced learning, pronunciation pedagogy, Uzbek high school students, artificial intelligence, automated speech recognition, digital feedback systems, segmental and suprasegmental features, learner autonomy, L2 phonology, computer-assisted language learning.